Application of Magneto-Rheological Fluids for Investigating the Effect of Skin Properties on Arterial Tonometry Measurements - Coon, Adam; Yang, Tae-Heon; Kim, Young-Min; Kang, Heeshin; Koo, Jeong-Hoi (Frontiers in Materials, 2019)
Accurate, non-invasive measurements of blood pressure and its continuous monitoring are extremely important for personal health care. Arterial tonometry, a method that is used to provide a detailed image of a patient’s cardiovascular health, shows promise for being a non-invasive alternative to current blood pressure measurement methods. However, its measurement accuracy is sensitive to patient variations such as the stiffness of the skin. Thus, this project intends to investigate the effect of skin properties (i.e., stiffness) on the accuracy of tonometric blood pressure measurements. To this end, a test platform, consisting of a pulsatile system and a tunable skin stiffness apparatus (or MR apparatus), is constructed. The cam-follower pulsatile system built based on in vivo testing of human pulses is used to generate realistic pulse waveforms. The MR apparatus is able to adjust its stiffness using Magneto-Rheological (MR) fluid whose apparent viscosity changes with applied magnetic fields. Placed at the surface of the MR apparatus, a cylinder with a frictionless plunger simulates a variable applanation force or “hold-down pressure” of tonometry by adjusting the added weights atop the cylinder. Using this test setup, a series of tests were performed by varying the input magnetic field and the weights, which effectively adjusts the skin stiffness and the hold-down pressure, respectively. The vertical displacement of the plunger caused by the internal pulse pressure was measured using a laser displacement sensor. The output displacement waveforms were analyzed with the focus on the peak amplitude difference of the waveforms, which is related to the augmentation index (a surrogate measure of arterial stiffness). The results show that there exists an “optimal” plunger weight or “hold-down pressure” that provides the most distinct output pulse waveforms. The results further show that the difference in the first two peak values decreases as the skin stiffness increases, indicating that the stiffer the skin property, the less the “hold-down pressure” effects on the accuracy of the tonometry measurements.